(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article is devoted to the analysis of military prose in Russian literature of the XX century as one of the leading thematic and artistic directions. The main stages of the development of military prose associated with the historical events of the century, as well as the key features of its poetics, are considered: documentary, moral issues, attention to the inner world of a person in war. Based on the works of Russian writers of the 20th century, changes in the interpretation of the image of war are revealed: from heroic and patriotic pathos to tragic and critical understanding of the military experience.